Public health research needs and challenges in transitional countries of South Eastern Europe (Italian Journal of Public Health, 2009)
The former communist countries of Southeastern Europe (SEE) are undergoing a rapid process oftransformation from state-enforced rigid economies to market-oriented societies. Compared with EuropeanUnion, SEE countries are characterized by higher death rates including not only infant mortality and maternaldeath, but also cardiovascular mortality and injuries. Yet, there is no sufficient research in SEE countriesdirected towards gaining a clear understanding of the health effects of transition and the fluctuations inhealth outcomes. A general characteristic in almost all SEE countries relates to the comparable problems theyface for engaging in research work which include: (i) lack of funds; (ii) lack of expertise, and; (iii) lack of “gooddata”. Nevertheless, there is an emergent need to improve research capacities in order to address and analyzeon a scientific basis the health problems and challenges in SEE countries. From this point of view, the Forumfor Public Health in South Eastern Europe (FPH-SEE: www.snz.hr/fph-see) seems a suitable network topromote, provide guidance and support different research activities and research projects in SEE countries.To increase the visibility of FPH-SEE network and to enhance its collaboration and active communication withEuropean academic institutions and donors, it was decided to establish an office near the Department ofInternational Health, Faculty of Health, Medicine and Life Sciences, Maastricht University, which will beresponsible for the coordination of the research network for SEE countries. This will help to promote researchfunding and to develop and strengthen research capacities in the SEE region.
Keywords: Policy making public health; research; southeast Europe